Ship Recycling Regulation in the European Union : How the current legislation will change and develop ship recycling market in the European Union - Kuusinen, Tuulia (My University, 2018)
Up to date recycling of most vessels flying the flags of European Union Member States have been dismantled in substandard conditions in South Asia. Various international and regional regulations have been established to control the vessel movement and improve the recycling conditions. The European Ship Recycling Regulation is the newest. The regulation’s aim is to control the recycling of the EU fleet by limiting the process to certified locations. Discussion has aroused from the required capacity supply to cost structure differences between different countries. The purpose of this thesis is to model the possible recycling market in the European Union. This includes understanding of the current recycling situation, what the required capacity would be in the future for EU and how the cost structure would differ from South Asian locations. In addition, it is important to overview what kind of methods there are for ship owners and ship recycling facilities to operate more efficiently and profitably. The current situation is described using descriptive statistics. Current situation is described by both understanding the average ages, mostly used locations and recycling volumes from a yearly development perspective. In addition, a closer look is taken to the vessels that have flown a European Union Member State flag and what the recycling industry currently seems to be in the European Union. A time series analysis is conducted to estimate the future capacity demand for ship recycling. Yearly increase pace has been estimated with OSL regression analysis. A sensitivity analysis has been conducted to understand whether there are differences in the cost structure inside the European Union. Also, different ways of adapting to the regulation are discussed basing on previous research and assumptions made from the data analysis results. Even though there are challenges in finding enough capacity and controlling the cost of recycling, the future is still seen as profitable due to the increasing demand of scrap metals, differentiation techniques and constantly improving processes.
Keywords: Ship recycling, Ship Recycling Regulation, European Commission, Environment, Cost model